Current opinions about using of medication intervention as neuroprotective therapy for degenerative ocular fundus diseases - Peng, Chun-Xia; Li, Gen-Lin (Chung-hua yen k'o tsa chih, 2012)
Recently, many studies indicated that certain medications can delay the apoptosis of retinal nerve cells at different points during the process of apoptosis and have neuroprotective effect on preventing degenerative ocular fundus diseases. N-methyl-D-aspartate receptor (NMDAR) antagonists, NMDAR-associated calcium channel blockers and acetylcholine receptor agonists have been shown to have neuroprotective effects for retinal damages by inhibiting NMDA-induced excitotoxicity. The inhibitors of nitric oxide synthase (NOS) can prevent the cell apoptosis and reduce the retinal cell loss by suppressing the activity of NOS as well as the production of the nitric oxide. Antioxidants and some Chinese traditional medicine with antioxidant activities can also have protective effect on retinal damage caused by degenerative ocular fundus diseases through their functions in decreasing the peroxidation reaction and the production of the superoxide radicals in the cells. In addition, activation of neurotrophic factor recept